Histopathological Change and Gene Expression of Heat Shock proteins (Hsp90 & Hsp70) in Snail pomaceacanaliculata (Lamarch, 1822) Exposed to Stress by the Pesticide Lannate - Ali A. A. Al-Ali1 , Murtatha Y. M. Al- Abbad1 , Basim K. Al-dhamin2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current study aimed to investigate the snail’s pathological changes and their relationship with the amount of gene expression of heat shock proteins HSP90 & HSP70 under the influence of lannate pesticide. canaliculata were collected during the period between 5th-10th May 2018. The laboratory generation snails were divided into 2 groups, the first was exposed to a concentration of 10 mg/L of the pesticide, as the lethal concentration of the pesticide was 12.6mg/L, and the second was left as a control group. After that, three snails from each group were dissected by the end of the following intervals (10mins, 1hr, 8hrs, 24hrs, 3days, 7days, and 15day). The gene expression was studies using qPCR method. Results of the genetic analysis for the abundance of the HSP70-HSP90 showed a clear effect of the pesticide on the treated snails during the above interval. On the other hand, the results of the histological study of the gills showed that the pathological changes varied in their intensity during the intervals, while there was no clear effect to variation of concentrations. These changes involve loss of cilia in the epithelial cells, infiltration of granulocytes in the cilia loss regions, hyperplasia, degradation and necrosis of cells as well as the accumulation of non-living brown and grey materials within the epithelial cells. Moreover, it was noticed that the mucous materials secreted from cystic cells has increased.